النظام القانوني لسلطات الضبط الاقتصادي في التشريع الجزائري - نقار نور الهدى- -شريفي كنزة (جامعة المسيلة, 2021)
سلطات الضبط المستقلة هي كيانات قانونية جديدة ظهرت في التشريع الجزائري منذ الانفتاح الاقتصادي الذي كرسه دستور 1989 وتبني الاقتصاد الحر الذي يقوم على فكرة انسحاب الدولة من الحقل الاقتصادي، لذلك جاءت هذه السلطات كبديل يجمع بين الحفاظ على خصوصيات قواعد السوق الحر القائم على المنافسة وضرورات ضبط المجال الاقتصادي من طرف الدولة عبر هذه الهيئات بما خوله لها المشرع الجزائري من صلاحيات تنظيمية وقمعية وأخرى غير قمعية حفاظا على النظام العام الاقتصادي الذي برز كأحد فروع النظام العام. Abstract: Independent judicial authorities are new legal entities that appeared in the Algerian legislature ,since Economic openness enshrined by the constitution of 1989.They build the free Economy , based upon the idea of the state withdrawal from the economic fields. Therefore , these authorities have come as an alternative combining the preservation of free market rules peculiarities, based on competition , and the necessity of controlling the economic filed by the state through these bodies, as empowered by the legislator, in matter of regulatory, repressive and other non-repressive power in order to maintain the economic public order which emerged as a branch of public order.
Keywords: • سلطات الضبط الاقتصادي، السلطات الادارية المستقلة. • Independent Administrative Authorities, Economic Control Authorities.